2006
DOI: 10.2174/138945006777709601
|View full text |Cite
|
Sign up to set email alerts
|

The Mechanism of Plasmid Curing in Bacteria

Abstract: Bacterial plasmids have a major impact on metabolic function. Lactose fermentation of E. coli or hemolysin B transporter expressed by the plasmids that carry these respective genes could be readily obviated by heterocyclic compounds that readily bind to plasmid DNA. These compounds could also reverse the resistance to antibiotics of E. coli, Enterobacter, Proteus, Staphylococcus and Yersinia strains by eliminating plasmids. However, the frequency and extent of this effect was significantly less than might have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
57
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(63 citation statements)
references
References 37 publications
(47 reference statements)
0
57
0
1
Order By: Relevance
“…The compounds identified could be used alone or in combination with existing antibiotics to treat recalcitrant bacterial infections. Other antibiotics and natural extracts have been reported to disrupt conjugative DNA transfer and the presence of plasmids within actively dividing bacterial cells (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15). In each case, however, the macromolecular target of those compounds was not understood and their mechanism of action has not been determined.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The compounds identified could be used alone or in combination with existing antibiotics to treat recalcitrant bacterial infections. Other antibiotics and natural extracts have been reported to disrupt conjugative DNA transfer and the presence of plasmids within actively dividing bacterial cells (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15). In each case, however, the macromolecular target of those compounds was not understood and their mechanism of action has not been determined.…”
Section: Discussionmentioning
confidence: 99%
“…Small-molecule inhibition of conjugation could prove to be a powerful method for curbing the generation and spread of multidrug-resistant strains. Past studies suggested that various antibiotics, polycyclic chemicals, and crude extracts inhibit conjugation at concentrations less than the antibacterial minimum inhibitory concentration (5-11); however, most of these effects have been attributed to nonconjugation-specific inhibition of bacterial growth or DNA synthesis (12)(13)(14)(15). This study describes a bottom-up approach used to identify the first small molecule inhibitors of conjugative DNA transfer that target an enzyme of the conjugative system.…”
mentioning
confidence: 99%
“…To determine if the resistance genes were carried by a plasmid, L. lactis 1A-1 was grown in MRS broth for 15 days in the presence of 10 g/ml acridine orange [12]. Following repeated exposure to the curing agent, the bacteria were diluted in MRS broth and spread on MRS agar plates.…”
Section: Curing Of Episomally Encoded Antimicrobial Resistancementioning
confidence: 99%
“…Agarose gel electrophoresis (Fig No:3) has shown relative decrease in plasmids of S aromaticum and K galanga treated extracts in comparison with sodium hypochlorite. Most of the efficient curing agents such as acridine orange, ethidium bromide or sodium dodecyl sulphate are toxic to mammals in one form or another which limits their therapeutic or industrial applications (Spengler et al, 2006). The plasmid curing potential of phytochemical is in accordance with the efficiency of heterocyclic compounds to bind differentially with different structures of DNA.…”
Section: Fluorescent Staining Of Pseudomonas Biofilmmentioning
confidence: 99%